2021
DOI: 10.3389/fphar.2021.756228
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Mitosis Delay and Apoptosis by CDDO-TFEA in Glioblastoma Multiforme

Abstract: Background: Glioblastoma multiforme (GBM) is the vicious malignant brain tumor in adults. Despite advances multi-disciplinary treatment, GBM constinues to have a poor overall survival. CDDO-trifluoroethyl-amide (CDDO-TEFA), a trifluoroethylamidederivative of CDDO, is an Nrf2/ARE pathway activator. CDDO-TEFEA is used to inhibit proliferation and induce apoptosis in glioma cells. However, it not clear what effect it may have on tumorigenesis in GBM.Methods: This in vitro study evaluated the effects of CDDO-TFEA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Therefore, CDDO and its derivatives have been used to treat chronic inflammatory diseases, such as Friedreich Ataxia [ 27 ] and chronic kidney disease [ 28 ]. Cytotoxic effects on tumor cells have been described for CDDO [ 29 ], derivatives that include CDDO-Me [ 30 ], CDDO-Im [ 20 ], CDDO-EA [ 20 ], CDDO-TFEA [ 22 , 23 ], and omaveloxolone [ 31 ] at moderate and high doses. As a result, CDDO and its derivatives could potentially exhibit anticancer activity at multiple levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, CDDO and its derivatives have been used to treat chronic inflammatory diseases, such as Friedreich Ataxia [ 27 ] and chronic kidney disease [ 28 ]. Cytotoxic effects on tumor cells have been described for CDDO [ 29 ], derivatives that include CDDO-Me [ 30 ], CDDO-Im [ 20 ], CDDO-EA [ 20 ], CDDO-TFEA [ 22 , 23 ], and omaveloxolone [ 31 ] at moderate and high doses. As a result, CDDO and its derivatives could potentially exhibit anticancer activity at multiple levels.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Kim et al [ 18 ] demonstrated that the ability of CDDO-Im to inhibit the BRCA1 mutant tumor G2/M cell cycle was associated with DNA damage followed by the activation of the DNA damage checkpoint. Finally, Tsai et al showed that induction of G2/M arrest in the cell cycle may be attributed to CDDO-TFEA treatment in established GBM8401 [ 23 , 36 ] and U87MG cells [ 22 , 36 ]. Taken together, these findings provide evidence that CDDO derivatives such as CDDO-dhTFEA induce cell cycle arrest in the G2/M phase, likely through the regulation of G2/M cell cycle genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation